miR-325-3p Reduces Proliferation and Promotes Apoptosis of Gastric Cancer Cells by Inhibiting Human Antigen R - Zhengwei Huang; Yacan Luo; Congcong Chen; Chaoyang Zhou; Zhengkang Su; Chang Cai; Xi Li; Wenzhi Wu (Canadian Journal of Gastroenterology and Hepatology)
Human antigen R (HuR), also known as ELAVL1, is a widely expressed RNA-binding protein (RBP) that has a significant impact on the development and advancement of tumors. Our previous study found that 5-fluorouracil (5-FU) may impede the proliferation and increase apoptosis in gastric cancer cells by reducing the nucleocytoplasmic shuttling of HuR. However, how posttranscriptional regulation influences HuR functions in gastric cancer remains to be elucidated. Here, we demonstrated that miR-325-3p has the potential to regulate the expression level of HuR by directly binding to its 3′UTR, which in turn led to a significant reduction in proliferation and an increase in apoptosis in gastric cancer cells. In addition, xenograft experiment showed that knockdown of HuR or overexpression of miR-325-3p group exhibited smaller tumor sizes after transplant of gastric cancer cells into zebrafish larvae. Thus, our findings offer new insights into the pathogenesis of gastric cancer and may potentially assist in identifying novel targets for drug therapy.